Analysis of oscillating water column technology in East Nusa Tenggara Indonesia - I Made Aditya Nugraha; I Gusti Made Ngurah Desnanjaya; Jhon Septin Mourisdo Siregar; Lebrina Ivantry Boikh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Utilization of new renewable energy can be one solution to the limitations of fossil energy. Ocean wave energy is renewable energy caused by tides, and this potential can be utilized as a source of electrical energy in Indonesia, especially East Nusa Tenggara. This ocean wave power plant uses oscillating water column (OWC) technology. This wave energy is energy that can be developed and environmentally friendly and available every time. This paper analyzes the amount of energy produced by ocean waves using OWC technology in the East Nusa Tenggara. The benefits of this paper can be used as a reference for planning the construction of a wave power plant around East Nusa Tenggara. The method used is to measure the condition of ocean waves for a year and analyze the amount of energy and electrical power that can be generated by ocean waves with the use of OWC. The results of the analysis show that the use of ocean wave power plants with OWC technology in the waters of East Nusa Tenggara can produce the highest energy of 20,291,728.83 Joules and the lowest is 17,062.62 Joules. The electrical power generated is between 3,645.45 Watt to 4,274,314.37 Watt, and average of power density by ocean waves using OWC is 19,021.89 Watt/m2.